Delayed Diagnosis of Olfactory Neuroblastoma During the SARS-CoV-2 Pandemic - Ryan Hess; Ryan P. McSpadden; Jingxin Qiu; Robert A. Fenstermaker (Annals of Internal Medicine: Clinical Cases)
The COVID-19 pandemic has resulted in a delay in cancer diagnosis and treatment during this time. A potential cause of delayed diagnosis that may be underrecognized is a patient misinterpretation of symptoms. To illustrate this point, we present the case of a patient with a delayed diagnosis of olfactory neuroblastoma 2 years after the onset of anosmia.